The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1186/1754-9493-7-4
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the current practice of the informed consent process in general surgery in the Netherlands

Abstract: BackgroundA properly conducted surgical informed consent process (SIC) allows patients to authorize an invasive procedure with full comprehension of relevant information including involved risks. Current practice of SIC may differ from the ideal situation. The aim of this study is to evaluate whether SIC practiced by Dutch general surgeons and residents is adequate with involvement of all required elements.MethodsAll members of the Dutch Society of Surgery received an online multiple choice questionnaire evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 35 publications
2
36
0
Order By: Relevance
“…Our study identified considerable deficiencies in the current knowledge and attitudes of our doctors toward this very crucial area of doctor-patient communication. Surprisingly certain studies from institutions in the western countries such as the USA, Europe, Netherlands and New Zealand have also reported a lack of doctors' knowledge regarding the process of SIC (1,3,(7)(8)(9)(10). Less than ideal level of working knowledge and attitudes regarding SIC on part of our doctors indicates a case for their focused education regarding SIC.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Our study identified considerable deficiencies in the current knowledge and attitudes of our doctors toward this very crucial area of doctor-patient communication. Surprisingly certain studies from institutions in the western countries such as the USA, Europe, Netherlands and New Zealand have also reported a lack of doctors' knowledge regarding the process of SIC (1,3,(7)(8)(9)(10). Less than ideal level of working knowledge and attitudes regarding SIC on part of our doctors indicates a case for their focused education regarding SIC.…”
Section: Discussionmentioning
confidence: 96%
“…The aim was to cover all fundamental aspects of the knowledge and relevant attitudes that surround the process of SIC and hence generate a representative data that could serve as a valid outcome variable. The questionnaire was prepared by consulting previously used and validated questionnaires employed by other researchers (3,(5)(6)(7)(8).…”
Section: Study Questionnairementioning
confidence: 99%
See 2 more Smart Citations
“…The patient has the right to obtain enough information regarding surgical procedures options. 1,2 In the twentieth century, the informed consent had been recognized as an issue in surgical health care services. 3 Informed consent is built on patient competence to understand information and making a deliberate decision to undergo a specific surgical procedure and is valid until the patient' disease has not been changed or no new findings that may change the planned procedure are revealed.…”
Section: Introductionmentioning
confidence: 99%